Jurassic PARK2: You eat your mitochondria, and you are what your mitochondria eat. Issue 3 (3rd March 2016) - Dorn, Gerald W.
ABSTRACT: Park2/Parkin is a central mediator of selective mitochondrial autophagy for mitochondrial quality control. We showed in mouse hearts that PINK1/Mfn2/Park2 mediated generalized mitophagy is essential to the normal perinatal transition from fetal mitochondria that prefer carbohydrates as metabolic substrates to adult fatty-acid metabolizing mitochondria. Our findings demonstrate how functional interactions between mitophagic mitochondrial removal and biogenic mitochondrial replacement facilitate metabolic maturation of the heart.